Exploring the Role of Foreign Investors in Russia's Local Currency Government Bond (OFZ) Market - Lu, Yinqiu (IMF Working Papers; Working Paper ;, 2017)
Local currency government bonds (OFZ bonds) are an important fixed-income instrument in Russia's financial markets. In this paper, based on granular data, we explore the development of the OFZ bond market with a focus on foreign investors. As this fixed-income market has experienced a liberalization of the domestic trading and settlement infrastructure, and weathered several episodes of market stresses since the 2008-09 global financial crisis, the role of foreign investors can be observed along with these events. What we have found is that foreign investors had influenced the market before they became an important player and since then they have contributed to the development of the market while not necessarily destabilizing it in episodes of shocks.